DeterminantsAirport Revenue and Total Passengers : Airport Access, Airport Service, Pandemic Covid 19, Airlines Characteristic, and Ticket Price - Azmieti Kurnia Sinta (PT FORMOSA CENDEKIA GLOBAL, 2023)
The goal is to test between variables X1-X5 with Y, and variables Y-Z, then the result is obtained only the variable ticket Price with the Total Passengers is insignificant, then the variable airport access with variable number of passengers is also insignificant, and variable Number of passengers with variable Airport Income is also insignificant. This research is based on tangible results in the field and at airports cannot be mentioned for any reason.